Web-Based Inventory Management Information System for Catholic Church - Simanjuntak, Agnes Gresti; Emerson Porman Malau, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid development of information technology encourages organizations, including religious institutions, to implement information systems that support operational activities. Inventory management at the Catholic Church of St. John the Baptist Perawang was previously conducted manually, resulting in recording errors, data duplication, and delays in report preparation. This study aims to design and develop a web-based inventory management information system using the Waterfall software development method. The development stages include requirement analysis, system design using Unified Modeling Language (UML), implementation using PHP and MySQL, and functional testing through Black-Box testing. The resulting system is capable of centrally managing inventory data, handling borrowing, returning, transfer, damage, and repair transactions, and generating structured reports automatically. The implementation results indicate that the system improves efficiency, data accuracy, and transparency in inventory management. The system provides an effective solution for supporting asset management and operational services within the church environment.